Minimal alterations in T-type calcium channel gating markedly modify physiological firing dynamics - Tscherter, A.; David, F.; Ivanova, T.; Deleuze, C.; Renger, J. J.; Uebele, V. N.; Shin, H-S.; Bal, T.; Leresche, N.; Lambert, R. C. (WILEY-BLACKWELL, 2011)
Non-technical summary Voltage-dependant calcium channels constitute a heterogeneous group playing ubiquitous roles in excitable cells. Among them the low-voltage activated T-type channels generate a family of currents that differ in their biophysical properties reflecting structural or neuromodulatory diversity. These T-type calcium channels are highly expressed in neurons located in the thalamus, a brain structure considered as the gateway to the cortex. Thalamic T-type calcium channels are critically involved in oscillatory neuronal activities associated with sleep or epilepsy and may contribute to sensory processing. Using injections of computer-simulated T-type conductances (a real time mimicry of ionic currents) in biological thalamic neurons, we dissect how the diversity in T-type currents impact on the output of thalamic neurons. We show that very subtle modifications in the properties of the T current that were overlooked so far affect drastically the physiological output of the thalamic neurons and therefore condition the dynamics of thalamo-cortical information integration.T-type calcium channel isoforms expressed in heterologous systems demonstrate marked differences in the biophysical properties of the resulting calcium currents. Such heterogeneity in gating behaviour not only reflects structural differences but is also observed following the regulation of channel activity by a number of ligands. However, the physiological impact of these differences in gating parameters of the T channels has never been evaluated in situ where the unique interplay between T-type calcium and other intrinsic currents is conserved, and T channel activation can be triggered by synaptic stimulation. Here, using the dynamic clamp technique, artificial T conductances were re-incorporated in thalamic neurons devoid of endogenous T currents to dissect the physiological role of the T current gating diversity on neuronal excitability. We demonstrate that the specific kinetics of the T currents in thalamocortical and nucleus reticularis thalami neurons determine the characteristic firing patterns of these neurons. We show that subtle modifications in T channel gating that are at the limit of the resolution achieved in classical biophysical studies in heterologous expression systems have profound consequences for synaptically evoked firing dynamics in native neurons. Moreover, we demonstrate that the biophysical properties of the T current in the voltage region corresponding to the foot of the activation and inactivation curves drastically condition physiologically evoked burst firing with a high degree of synaptic input specificity.
Keywords: NEURONS-IN-VITRO; THALAMOCORTICAL RELAY NEURONS; THALAMIC NEURONS; CA2+ CHANNELS; DIFFERENTIAL DISTRIBUTION; FUNCTIONAL-PROPERTIES; SPLICE VARIANTS; MOUSE-BRAIN; CELLS; EXPRESSION